Functional fitness and falls in older adults on haemodialysis - Sims, Rebecca J.A. (2011)
The number of older adults with end stage renal failure is rapidly increasing. Over the last 30 years, attitudes, technologies, resources and the premorbid health status of older adults have evolved and dialysis is now being offered routinely to this group. Dialysis is a life maintaining treatment but is demanding physically and psychologically and these burdens interplay with the normal consequences of aging. To ensure length of life is not preserved at the expense of quality requires focus on the interactions of end stage renal disease (ESRD), renal replacement therapy (RRT) and ageing-related problems, such as immobility and falls. However, despite these considerations being specifically referenced in national policy and recognised amongst dialysis groups internationally, there is limited literature regarding the specific and specialised needs of this patient group or guidance on focussed service development within the United Kingdom.